The genome sequence of African rice (Oryza glaberrima) and evidence for independent domestication - Wang, M.; Yu, Y.; Haberer, G.; Marri, P.R.; Fan, C.; Goicoechea, J.L.; Zuccolo, A.; Song, X.; Kudrna, D.; Ammiraju, J.S.S.; Cossu, R.M.; Maldonado, C.; et al. (Springer, 2014)
The cultivation of rice in Africa dates back more than 3,000 years. Interestingly, African rice is not of the same origin as Asian rice (Oryza sativa L.) but rather is an entirely different species (i.e., Oryza glaberrima Steud.). Here we present a high-quality assembly and annotation of the O. glaberrima genome and detailed analyses of its evolutionary history of domestication and selection. Population genomics analyses of 20 O. glaberrima and 94 Oryza barthii accessions support the hypothesis that O. glaberrima was domesticated in a single region along the Niger river as opposed to noncentric domestication events across Africa. We detected evidence for artificial selection at a genome-wide scale, as well as with a set of O. glaberrima genes orthologous to O. sativa genes that are known to be associated with domestication, thus indicating convergent yet independent selection of a common set of genes during two geographically and culturally distinct domestication processes.